The association between hyperuricemia and coronary artery calcification development: A systematic review and meta‐analysis. Issue 11 (30th September 2019) - Liang, Ling; Hou, Xianghua; Bainey, Kevin R.; Zhang, Yanlin; Tymchak, Wayne; Qi, Zhongquan; Li, Weihua; Banh, Hoan Linh
Abstract: Hyperuricemia coincides with coronary artery calcification (CAC) development, but the role of serum uric acid (SUA) as a risk factor for CAC remains unclear. The objective of this study was to gain an insight into the association between SUA and CAC in adults by performing a meta‐analysis. MEDLINE, EMBASE, the Cochrane Library, and EBSCO (CINAHL) were searched for relevant observational studies published until 2 June 2019. Studies were included only if they reported data on CAC presence (Agatston score > 0) or progression related to hyperuricemia in subclinical adult patients. The pooled estimates of crude and adjusted odds ratios (ORs) and 95% confidence interval (CI) were calculated to evaluate the association between CAC presence or progression and hyperuricemia. A total of 11 studies were identified involving 11 108 adults. The pooled OR based on the frequency of CAC presence showed that patients in the high SUA group had 1.806‐fold risk for developing CAC (95% CI: 1.491‐2.186) under the minimal threshold of hyperuricemia (more than 6 mg/dL or 357 μmoL/L). When SUA levels were analyzed as categorical variables, the pooled estimate of adjusted ORs was 1.48 (95% CI: 1.23‐1.79) for CAC presence. Additionally, for each increase of 1 mg/dL of SUA level, the risk of CAC progression was increased by 31% (95% CI: 1.15‐1.49) with an average follow‐up duration ranged from 4.6 to 6.1 years. Hyperuricemia is closely associated with increased risk of CAC development and CAC progression in asymptomatic patients.